Autonomic Self‐Healing of PEDOT:PSS Achieved Via Polyethylene Glycol Addition. (13th May 2020) - Li, Yang; Li, Xinda; Zhang, Shiming; Liu, Leslie; Hamad, Natalie; Bobbara, Sanyasi Rao; Pasini, Damiano; Cicoira, Fabio
Abstract: Self‐healing electronic materials are of primary interest for bioelectronics and sustainable electronics. In this work, autonomic self‐healing of films obtained from mixtures of the conducting polymer poly(3, 4‐ethylenedioxythiophene) doped with polystyrene sulfonate (PEDOT:PSS) and polyethylene glycol (PEG) is reported. The presence of PEG in PEDOT:PSS films decreases the elastic modulus and increases the elongation at break, thus leading to a softer material with enhanced self‐healing characteristics. In situ imaging of the cutting/healing process shows that the healing mechanism is likely due to flowing back of the material to the damaged area right after the cutting. Abstract : Films processed from mixtures of poly(3, 4‐ethylenedioxythiophene) doped with polystyrene sulfonate (PEDOT:PSS) and polyethylene glycol show autonomic self‐healing when cut with a sharp blade.